Punishment from the Manager's Perspective: A Grounded Investigation and Inductive Model - Butterfield, Kenneth D.; Treviño, Linda Klebe; Ball, Gail A. (Academy of Management Journal, 1996)
We employed a qualitative interview technique to develop an inductive model of punishment from a managerial perspective. Findings suggest that managers feel pressure from a variety of sources?organizations, work groups, punished subordinates, and themselves. Managers are also aware that punishment is a highly charged cognitive and emotional event with broad and far-reaching effects that range well beyond punished subordinates and simply changing their attitudes and behaviors.